DETERMINAN KUNJUNGAN PARIWISATA ASEAN (INDONESIA, THAILAND, MALAYSIA, SINGAPURA, VIETNAM, FILIPINA, KAMBOJA, LAOS, MYANMAR, BRUNEI DARUSSALAM) - Al Qudusi, Zuhuurul Asror; Agung Gunanto, Edy Yusuf (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
ASEAN regional economic integration under the ASEAN Economic Community (AEC) prioritizes the tourism sector as a single market and an important component of the economy of all ASEAN member countries for equitable development in the country. Research related to tourism focuses more on the analysis of determinants at the country level. There are not many studies related to the determinants of tourism at the regional level, especially in ASEAN. This study aims to analyze the factors that influence the level of tourist arrivals in the ASEAN region. The data used is secondary data with panel data method. This study uses Generalized Least Square regression to analyze the level of tourist visits as the dependent variable, and five independent variables, namely income, tourism prices, physical investment, country risk, and internet usage. The results showed that the significant influencing factors were tourism prices, physical investment, and internet usage. Meanwhile, income and country risk did not significantly affect the number of tourist arrivals.